Alternanthera mosaic potexvirus: Several Features, Properties, and Application - Ekaterina Donchenko; Ekaterina Trifonova; Nikolai Nikitin; Joseph Atabekov; Olga Karpova (Advances in Virology)
Alternanthera mosaic virus (AltMV) is a typical member of the Potexvirus genus in its morphology and genome structure; still it exhibits a number of unique features. They allow this virus to be considered a promising object for biotechnology. Virions and virus-like particles (VLPs) of AltMV are stable in a wide range of conditions, including sera of laboratory animals. AltMV VLPs can assemble at various pH and ionic strengths. Furthermore, AltMV virions and VLPs demonstrate high immunogenicity, enhancing the immune response to the target antigen thus offering the possibility of being used as potential adjuvants. Recently, for the first time for plant viruses, we showed the structural difference between morphologically similar viral and virus-like particles on AltMV virions and VLPs. In this review, we discuss the features of AltMV virions, AltMV VLP assembly, and their structure and properties, as well as the characteristics of AltMV isolates, host plants, infection symptoms, AltMV isolation and purification, genome structure, viral proteins, and AltMV-based vectors.